Sublethal Toxicity of Acid Orange 7 in the Freshwater fish, Anabas testudineus (Bloch, 1792), and the Role of Vitamin C as Antioxidant in the Prevention of Oxidative Stress - Priyatha, C. V.; Chitra, K. C. (International Journal of Scientific Research in Biological Sciences, 2019)
Sublethal toxic effects of acid orange 7 on antioxidant status and histology of liver, kidney and muscle tissues, and the protective role of vitamin C were examined in Anabas testudineus. Acid orange 7 at 0.27 g/ L concentration was exposed for 24, 72 and 96 h followed by vitamin C (0.55 g/ L concentration) for 7 days. Activities of superoxide dismutase, catalase, glutathione reductase, and levels of hydrogen peroxide (H2O2) generation and lipid peroxidation (LPO) were evaluated in the liver, kidney and muscle tissues. The results showed significant (P<0.05) reduction in the activities of antioxidant enzymes with concomitant increase in the levels of H2O2 and LPO thereby indicated the induction of oxidative stress. Activities of alanine and aspartate aminotransferases in liver and kidney, and acid and alkaline phosphatase in muscle tissue also decreased significantly (P<0.05) in the treatment groups due to the sublethal toxicity of acid orange 7. Histopathological examination revealed severe damage in all tissues however, the damage was not fully recovered after vitamin C exposure. Interestingly, vitamin C exposure neutralized the toxic effects of acid orange 7 as evident by normalizing the activities of all antioxidant enzymes thereby proved the protection of tissues against oxidative stress.